Exploring Participants' Experiences of an 8-Week Mindfulness-Based Stress Reduction (MBSR) Program in the Context of Adapting to Living with Chronic Pain - Hladkowicz, Emily (Université d'Ottawa / University of Ottawa, 2016)
At least one in five Canadians lives with chronic pain, and the prevalence rate is rising. Chronic pain can be a result of injury, disease, surgery, and in some cases, the cause remains unknown. Due to the complexity and variability in the etiology and presentation of chronic pain, it can often be a challenge to implement an appropriate and effective treatment plan. Often, the effects of chronic pain are so debilitating that relief is only available temporarily with pain medication. However, there is the concern and possibility of addiction, health issues, and even increased risk of death with some medicinal interventions. Living with chronic pain can have widespread ramifications, affecting more than just the physical body. This includes psychological, emotional, interpersonal, and vocational challenges. In essence, all aspects of one’s quality of life can be affected by chronic pain. As chronic pain often persists over many years or even the lifetime, it is important to better understand how one might adapt to living with chronic pain. Mindfulness-Based Stress Reduction (MBSR) is a structured 8-week program that is commonly used as an intervention for people living with chronic pain, as several research studies have shown promising effects on pain outcomes and quality of life. Using hermeneutic phenomenology, the purpose of this study is to learn about the lived experiences of participating in an 8-week MBSR program from those living with chronic pain. Particularly, it explores how, if at all, an MBSR program may play a role in the participants’ adaptation to living with chronic pain. In depth semi-structured interviews were conducted with 3 participants at the end of the MBSR program. They were then analyzed, interpreted and checked by the researcher. The interpretative analysis involved the researcher explicitly detailing their own positioning in order to inform the interpretations and allow for a well-informed continued interpretation and understanding from readers. Overall, participants described several key aspects which may shed light into the benefits that MBSR can have in regards to adaptation to chronic pain as delineated by the following categories: physical pain and pain management, self-perception and identity, relationship dynamics, and emotional equilibrium. Lastly, broader themes included: being heard and understood, letting go and being here, the healing perspective, and moving from surviving to living. The results of this study speaks to the experience of living with chronic pain, and how an MBSR program offers the tools to help facilitate the adaptation process to living with chronic pain, thereby improving quality of life.
Keywords: chronic pain; mindfulness; mindfulness-based stress reduction; psychosocial adaptation